Inhibitory effect of melatonin on necroptosis via repressing the Ripk3‐PGAM5‐CypD‐mPTP pathway attenuates cardiac microvascular ischemia–reperfusion injury. Issue 3 (28th May 2018) - Zhou, Hao; Li, Dandan; Zhu, Pingjun; Ma, Qiang; Toan, Sam; Wang, Jin; Hu, Shunying; Chen, Yundai; Zhang, Yingmei
Abstract: The molecular features of necroptosis in cardiac ischemia–reperfusion (IR) injury have been extensively explored. However, there have been no studies investigating the physiological regulatory mechanisms of melatonin acting on necroptosis in cardiac IR injury. This study was designed to determine the role of necroptosis in microvascular IR injury, and investigate the contribution of melatonin in repressing necroptosis and preventing IR‐mediated endothelial system collapse. Our results demonstrated that Ripk3 was primarily activated by IR injury and consequently aggravated endothelial necroptosis, microvessel barrier dysfunction, capillary hyperpermeability, the inflammation response, microcirculatory vasospasms, and microvascular perfusion defects. However, administration of melatonin prevented Ripk3 activation and provided a pro‐survival advantage for the endothelial system in the context of cardiac IR injury, similar to the results obtained via genetic ablation of Ripk3. Functional investigations clearly illustrated that activated Ripk3 upregulated PGAM5 expression, and the latter increased CypD phosphorylation, which obligated endothelial cells to undergo necroptosis via augmenting mPTP (mitochondrial permeability transition pore) opening. Interestingly, melatonin supplementation suppressed mPTP opening and interrupted endothelial necroptosis via blocking the Ripk3‐PGAM5‐CypD signal pathways. Taken together, our studies identified the Ripk3‐PGAM5‐CypD‐mPTP axis as a new pathway responsible for reperfusion‐mediated microvascular damage via initiating endothelial necroptosis. In contrast, melatonin treatment inhibited the Ripk3‐PGAM5‐CypD‐mPTP cascade and thus reduced cellular necroptosis, conferring a protective advantage to the endothelial system in IR stress. These findings establish a new paradigm in microvascular IR injury and update the concept for cell death management handled by melatonin under the burden of reperfusion attack.